ä¸¹æˆŽå¸ƒæ‹‰å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯æ•™è‚²ä¸“ä¸š2019å±Šå¦ç”Ÿå¯¹åŒä¹‰è¯"è¿žç»"å’Œ"é™†ç»"çš„ä½¿ç”¨åè¯¯åˆ†æž - Deriska, Veliyana; Ina, Ina; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Synonyms refer to words that have the same or similar meanings, as in the words "liánxù" and "lùxù". "Liánxù" and "lùxù" both have a similar meaning, which means something that happens continuously. However, these two words have different meanings and uses. To understand what mistakes and difficulties were experienced by Chinese Language Education Students of the FKIP UNTAN batch of 2019 in using the words "liánxù" and "lùxù", the author conducted research using the literature review method and the test method. The test results showed that the students did not have a good mastery of using the synonyms "liánxù" and "lùxù". Through multiple choice questions, true-false questions, and translation questions, it can be seen that students are wrong in choosing the correct vocabulary for using the word "liánxù", the error rate is 38%. Error in ordering sentences as much as 19.7%. The error of omission rate is as much as 6.7%. Meanwhile, the error in choosing the correct vocabulary in using the word "lùxù" is 44.7%. Error in ordering sentences is 27.5%. the error of omission is 11%. This may lead to students having the highest average error in using the Chinese synonym "lùxù". The reasons for student errors are negative transference from the mother tongue, generalization of target language rules, and use of communicative strategies. This shows that there are still many students who do not understand the meaning, use, and differences between "liánxù" and "lùxù".